CONFIGURATION OF PERSONNEL MARKETING BASED ON MARKET RESEARCH INTERNAL LABOR MARKET (Revista Inclusiones, 2020)
In modern conditions, traditional marketing technologies are used for marketing the internal labor market: emphasis on the partner and behavioral factors, influence on the situation, comprehensive collection and processing of information, monitoring changes in social values, etc. The relevance and timeliness of marketing of the internal labor market is emphasized by the following points: a number of market actors interact with other agents as employers, so it is marketing that will allow them to become informed and effective in social and labor interaction. It is marketing that determines: configuration of technologies for the formation, distribution and use of human resources based on the analysis and synthesis of information; diagnostics of labor market conditions; formalization of facts about the volume, dynamics and structure of professions and specialties; formation of public relations.